2006
DOI: 10.1590/s1807-59322006000400006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Autoimmune Thyroiditis in the Urban Area Neighboring a Petrochemical Complex and a Control Area in Sao Paulo, Brazil

Abstract: PURPOSE: To evaluate the prevalence of chronic autoimmune thyroiditis in 2 urban areas of metropolitan São Paulo (Brazil): Polo Area neighboring a large petrochemical complex and São Bernardo Campo Area (control area). SUBJECTS AND METHODS: Subjects were randomly included from the adult population (20 to 70 years of age) of both genders (women 80%, men 20%) who voluntarily agreed to participate. From the Polo Area, in the vicinity of a large petrochemical industrial complex, 409 subjects were included; from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 23 publications
2
13
0
7
Order By: Relevance
“…Two Brazilian groups (12,13) have addressed the association of HT with the petrochemical complex-related pollution by targeting the same area surrounding the petrochemical complex of Capuava (municipality of Santo André, State of Sao Paulo), but two different control areas, though both control areas were located at similar distance (about 16 km away from the complex). Results differed because the rate of the endocrine diagnosis of HT was similar to that of the control area (15.6% vs 19.5%) in one study (12) and it was twofold greater (9.3% vs 3.9%) in the other study (13).…”
Section: Discussionmentioning
confidence: 99%
“…Two Brazilian groups (12,13) have addressed the association of HT with the petrochemical complex-related pollution by targeting the same area surrounding the petrochemical complex of Capuava (municipality of Santo André, State of Sao Paulo), but two different control areas, though both control areas were located at similar distance (about 16 km away from the complex). Results differed because the rate of the endocrine diagnosis of HT was similar to that of the control area (15.6% vs 19.5%) in one study (12) and it was twofold greater (9.3% vs 3.9%) in the other study (13).…”
Section: Discussionmentioning
confidence: 99%
“…Although this study has some limitations, it points to the fact that excessive iodine intake may be linked to a higher prevalence of thyroid cancer as compared to populations with low or adequate Iodine nutrition (85). More recently, Camargo et al (86) studied urinary excretion of iodine, thyroid function tests, thyroid antibodies and sonographic characteristics of 829 inhabitants of a suburban area of great São Paulo city. This population had been on excessive iodine intake (59.5% excreted more than 300 µg Iodine/L of urine) for six years (1998)(1999)(2000)(2001)(2002)(2003).…”
Section: Iodine Intake and Thyroid Cancermentioning
confidence: 91%
“…Camargo et al found a similar rate of chronic thyroiditis among 829 individuals from a general population in the city of São Paulo (17.6%). 28 The frequency of angioedema in the CIU group (60.9%)…”
Section: Discussionmentioning
confidence: 98%